Highly Efficient Electrosynthesis of Urea from CO2 and Nitrate by a Metal–Organic Framework with Dual Active Sites - Qiu, Xiao‐Feng; Huang, Jia‐Run; Yu, Can; Chen, Xiao‐Ming; Liao, Pei‐Qin (Angewandte Chemie International Edition, 2024)
Electrosynthesis of urea from CO2 and NO3− is a sustainable alternative to energy‐intensive industrial processes. The main challenge hindering the progress of this technology lies in the development of advanced electrocatalysts that efficiently utilize abundant, low‐cost CO2 and nitrogen sources to yield urea with both high Faradaic efficiency (FE) and current density. In this work, we designed and prepared a new two‐dimensional metal–organic framework (MOF), namely PcNi−Fe−O, constructed by nickel‐phthalocyanine (NiPc) ligands and square‐planar FeO4 nodes, as the electrocatalyst for urea electrosynthesis. PcNi−Fe−O exhibits remarkable performance to yield urea at a high current density of 10.1 mA cm−2 with a high FE(urea) of 54.1 % in a neutral aqueous solution, surpassing those of most reported electrocatalysts. No obvious performance degradation was observed over 20 hours of continuous operation at the current density of 10.1 mA cm−2. By expanding the electrode area to 25 cm2 and operating for 8 hours, we obtained 0.164 g of high‐purity urea, underscoring its potential for industrial applications. Mechanism study unveiled the enhanced performance might be ascribed to the synergistic interaction between NiPc and FeO4 sites. Specifically, NH3 produced at the FeO4 site can efficiently migrate and couple with the *NHCOOH intermediate adsorbed on the urea‐producing site (NiPc). This synergistic effect results in a lower energy barrier for C−N bond formation than those of the reported catalysts with single active sites. The main challenge for urea electrosynthesis is to operate at both high Faradaic efficiency (FE) and current density. Here, we report a sustainable method for urea electrosynthesis from CO2 and NO3− using a novel MOF catalyst, PcNi−Fe−O, achieving high efficiency and stability, and demonstrating potential for industrial scale‐up.